2020
DOI: 10.2196/17491
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Low-Cost Portable 3D Virtual Reality Gesture-Mediated Simulator for Training and Learning Basic Psychomotor Skills in Minimally Invasive Surgery: Development and Content Validity Study

Abstract: Background Simulation in virtual environments has become a new paradigm for surgeon training in minimally invasive surgery (MIS). However, this technology is expensive and difficult to access. Objective This study aims first to describe the development of a new gesture-based simulator for learning skills in MIS and, second, to establish its fidelity to the criterion and sources of content-related validity evidence. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 164 publications
(118 reference statements)
0
18
0
Order By: Relevance
“…Another way to control for the wow-effect would be running the experiment with experienced VR headset users. Lastly, while this study chose to conceptualize learning as memorization, other forms of learning (i.e., psychomotor or embodied learning) might be of interest for future research (Seo et al, 2018;Alvarez-Lopez et al, 2020). In addition, the VR environment in this study was simulating a place illusion in a pointandclick manner which is highly similar to a traditional screen usage, while plausibility illusion or agency in the VR world has not been assessed but might be of interest for future research (Slater, 2017;Gruber and Kaplan-Rakowski, 2020;Hurault et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another way to control for the wow-effect would be running the experiment with experienced VR headset users. Lastly, while this study chose to conceptualize learning as memorization, other forms of learning (i.e., psychomotor or embodied learning) might be of interest for future research (Seo et al, 2018;Alvarez-Lopez et al, 2020). In addition, the VR environment in this study was simulating a place illusion in a pointandclick manner which is highly similar to a traditional screen usage, while plausibility illusion or agency in the VR world has not been assessed but might be of interest for future research (Slater, 2017;Gruber and Kaplan-Rakowski, 2020;Hurault et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from the survey assessing fidelity to the criterion and content-related validity evidence for SIMISGEST-VR showed that all 30 participants felt that most aspects of the simulator were adequately realistic and that it could be used as a tool for teaching basic psychomotor skills in laparoscopic surgery (Likert score: range 4.07-4.73). The sources of content-related validity evidence showed that our simulator was a reliable training tool and that the tasks enabled learning of the basic psychomotor skills required in minimally invasive surgery (Likert score: range 4.28-4.67) [53].…”
Section: Methodsmentioning
confidence: 99%
“…These countries face barriers to incorporate simulated training including high costs, finding an appropriate training environment, and storage of cadaveric and animal material [ 15 ]. However, development of virtual learning platforms, remote tele-simulation [ 34 ], and the development of low-cost high-fidelity VR platforms [ 4 , 50 ] could broaden opportunities for education. Our findings showed that synthetic and virtual platforms have been used to simulate key neurosurgical procedures, further demonstrating their applicability in low- and middle-income countries.…”
Section: Covid-19 and Simulation Models In Neurosurgerymentioning
confidence: 99%